Comparative Study Of Software And Hardware Solutions For Partial Shading In PV System - Zainal, Salam; Mohd Zulkifli, Ramli; Jubaer, Ahmed (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
The energy yield of the PV system is reduced significantly due to partial shading. To mitigate this problem, two approaches, namely the software and hardware solutions are introduced by many researchers. However, no effort thus far has been made to compare their performances. This paper carries out the evaluation of the particle swarm optimization (software solution) and the energy recovery circuit (hardware solution), by subjecting them to various partial shading conditions. The results are benchmarked with the conventional perturb and observe method. It is found that the hardware approve exhibits higher energy yield. However, this is archived with the expense of additional components.